Foley as storytelling : internship at studio Sound Troop - Llona, Lucía Alejandra Beaumont (2024)
This report reflects on the experiences and skills acquired during the curricular internship focused on foley art at the studio Sound Troop in Santiago de Compostela, Spain. Over the course of the six months internship, I applied the knowledge learned during the Sound and Image Master’s Program and refined my abilities in foley editing, recording, mixing and performance, which are reviewed in detail in this report. The document includes an analysis of the studio foley stage, explaining how Sound Troop controls the acoustics of the room to achieve the desired sound, and concluding that this recording technique prioritizes the naturalistic and aesthetical elements of the craft. Additionally, the report offers reflections on the artistic and storytelling aspects of foley, addressing the concerns about the intersection of artificial intelligence with the human made foley. As an artist, the objective with this dissertation is to show the possibilities and concerns surrounding foley today, and how it can be integrated into artistic practice.